3D two-photon microprinting of nanoporous architectures - Mayer, Frederik; Ryklin, Daniel; Wacker, Irene; Curticean, Ernest Ronald; Čalkovský, Martin; Niemeyer, Andreas; Dong, Zheqin; Levkin, Pavel A.; Gerthsen, Dagmar; Schröder, Rasmus R.; Wegener, Martin (Advanced materials, 2020)
A photoresist system for 3D two-photon microprinting is presented, which enables the printing of inherently nanoporous structures with mean pore sizes around 50 nm by means of self-organization on the nanoscale. A phase separation between polymerizable and chemically inert photoresist components leads to the formation of 3D co-continuous structures. Subsequent washing-out of the unpolymerized phase reveals the porous polymer structures. To characterize the volume properties of the printed structures, scanning electron microscopy images are recorded from ultramicrotome sections. In addition, the light-scattering properties of the 3D-printed material are analyzed. By adjusting the printing parameters, the porosity can be controlled during 3D printing. As an application example, a functioning miniaturized Ulbricht light-collection sphere is 3D printed and tested.